2021
DOI: 10.21101/cejph.a6117
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection at work? Vitamin D deficiency rates and rising health problems in young Turkish Cypriot professionals

Abstract: Objectives: Vitamin D is a fat-soluble, prohormone vitamin that is important especially for bone mineralization and skeletal health. In recent years, vitamin D deficiency appeared as a worldwide problem, affecting many people in different ways including the Northern Cypriot population. The deficiency might be caused by the lack of exposure to sunlight, diet low in vitamin D, sedentary lifestyle, and also due to some genetic variations in the vitamin D receptor (VDR) gene.Methods: In this study, four common VDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…13 Limited sun exposure, advanced age, a sedentary lifestyle, and vitamin D receptor (VDR) gene polymorphisms might be the factors linked to a greater risk of vitamin D deficiency diseases. 14 However, a recent study showed that the young Turkish Cypriots population in Northern Cyprus was found to be vitamin D deficient, despite the fact that the Island of Cyprus receives constant sunlight for almost 9 months a year, and the Mediterranean diet is rich in vitamin D-containing foods. 14,15 Moreover, the polymorphisms on the VDR gene included the most well-known TaqI-rs731236 T > C, ApaI-rs7975232 A > C, BsmI-rs1544410 G > A, and FokI-rs10735810 C > T, which were associated with secretion of vitamin D and a higher risk of chronic diseases like autoimmune diseases, type 2 diabetes, and cancer.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…13 Limited sun exposure, advanced age, a sedentary lifestyle, and vitamin D receptor (VDR) gene polymorphisms might be the factors linked to a greater risk of vitamin D deficiency diseases. 14 However, a recent study showed that the young Turkish Cypriots population in Northern Cyprus was found to be vitamin D deficient, despite the fact that the Island of Cyprus receives constant sunlight for almost 9 months a year, and the Mediterranean diet is rich in vitamin D-containing foods. 14,15 Moreover, the polymorphisms on the VDR gene included the most well-known TaqI-rs731236 T > C, ApaI-rs7975232 A > C, BsmI-rs1544410 G > A, and FokI-rs10735810 C > T, which were associated with secretion of vitamin D and a higher risk of chronic diseases like autoimmune diseases, type 2 diabetes, and cancer.…”
mentioning
confidence: 99%
“…14 However, a recent study showed that the young Turkish Cypriots population in Northern Cyprus was found to be vitamin D deficient, despite the fact that the Island of Cyprus receives constant sunlight for almost 9 months a year, and the Mediterranean diet is rich in vitamin D-containing foods. 14,15 Moreover, the polymorphisms on the VDR gene included the most well-known TaqI-rs731236 T > C, ApaI-rs7975232 A > C, BsmI-rs1544410 G > A, and FokI-rs10735810 C > T, which were associated with secretion of vitamin D and a higher risk of chronic diseases like autoimmune diseases, type 2 diabetes, and cancer. 16,17 Studies on the associations of COVID-19 prevalence and mortality rates and genetic variability of the hosts showed that VDR gene polymorphisms may play role in modulating COVID-19 infection and might be related to the survival of the patients and COVID-19 severity.…”
mentioning
confidence: 99%
See 2 more Smart Citations